Wavelet technique based islanding detection and improved repetitive current control for reliable operation of grid-connected PV systems. (May 2015) - Pinto, Smitha Joyce; Panda, Gayadhar
Highlights: Plug-in repetitive current control strategy employed for grid connected inverter system. Comparative performance analysis of plug-in RC controller with existing PI and PR controller. Wavelet technique applied for reliable islanding detection. Abstract: Recent years have witnessed a thrust towards the use of solar energy as the major renewable energy source for distributed power generation. The proposed system requires reliable detection technique and suitable current control strategy for proper operation. This paper focuses on plug-in repetitive current (RC) control strategy for grid connected inverter system and wavelet technique for electrical grid status identification. The performance of proposed current control technique employed for grid connected inverter system under distorted and unbalanced grid voltage is compared with the existing conventional methods like PI and PR controller. This controller uses the feedback control system for attenuating periodic disturbances, improving high quality sinusoidal output current and high power factor. The proposed scheme employs fourth order infinite impulse response (IIR) filter for maintaining its resonance frequency, output frequency matching with grid fundamental frequency and reduction of harmonics. The DC-DC boost converter implements incremental conductance based (INC) maximum power point tracker (MPPT) algorithm. The effects of LCL filter for improving disturbance rejection capability and dynamic performance of the proposed system is also demonstrated. Grid connected PV inverter employs wavelet technique for an islanding detection functionality in order to determine the status of the electrical grid. In order to show the effectiveness of the proposed algorithm, modeling and simulation for grid connected PV system is performed using MATLAB/SIMULINK and its PowerSim toolbox.